The case for tying specialty status to completion of dental residency: Dental education's stake. Issue 8 (8th March 2020) - Fields, Henry W.; Casamassimo, Paul; Owsiany, David J.; Saperstein, Martin
Abstract: Background: The American Dental Association's (ADA) specialty recognition process has long been the gold standard in dentistry. Specialty advertising regulations have been challenged as inconsistent with commercial speech rights of dentists wishing to advertise as specialists in areas not recognized as ADA specialties. Commission of Dental Accreditation‐approved postdoctoral education exists to support this process using standard‐based education, continuous quality review and accountability. Purpose: In 2017, a federal court declared Texas dental specialty advertising rules unconstitutional noting the state did not present evidence demonstrating the public was being misled. A state dental association commissioned a professional survey to assess state residents' understanding of the term "specialist" in dental advertising. Methods: Telephone interviews conducted with 812, 18+‐year‐old Ohio residents focused on advertising related to dental implants and TMJ disorders (not recognized specialties) and orthodontics and oral surgery (recognized specialties). Results: Respondents indicated they would be inclined to think a dentist who advertised as a specialist had completed an accredited dental residency program and was more qualified to perform specialty care than a general dentist. Respondents also indicated that they would be less likely to choose a dentist who advertised as a specialist who did not have accredited residency training. Conclusions: Tying specialty status to completion of a residency program accredited by an agency recognized by the U.S. Department of Education is important to the public's expectations and has implications for dental education.